Industri Pengolahan Hasil Ternak Ayam Pedaging (Broiler) di Kabupaten Sidenreng Rappang - Muh.Yuzril Dharmansyah; Usman Usman; Ahmad Nadhil Edar (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Broiler chicken processing in Sidenreng Rappang Regency, one of the largest chicken meat producers in Indonesia, plays an important role in providing 65% of national animal protein, supporting global food security. However, broiler chicken production in this district experienced significant fluctuations between 2018-2023, with the lowest decline in 2023 (1,587,650 heads). This industry faces challenges such as limited infrastructure (roads, electricity, storage), compliance with food safety standards, and lack of skilled workers in processing technology. This study aims to design a broiler chicken processing industry with an environmental architecture approach that supports efficient production, distribution, and environmentally friendly waste management. Using qualitative descriptive analysis methods, the design is directed at meeting quality standards, increasing global competitiveness, and supporting national food self-sufficiency through logistical, accessible, and sustainable facilities.